1989
DOI: 10.1159/000125154
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Inhibitory Action of 2-Deoxy-Glucose on Thyroid Hormone Secretion in the Mouse

Abstract: The thyroid gland is richly innervated but the effects of activation of these nerves on thyroid hormone secretion are not yet established. In the present study, intravenous injection to mice of 2-deoxy-glucose (2-DG; 60 µmol/animal) was used to activate the autonomic nerves. The nerve activation occurs through the neuroglycopenia. We found that 2-DG inhibited the thyroid-stimulating hormone (TSH; 70 µU/animal)-induced thyroid hormone secretion, measured as release of radioiodine bound to anti-T4 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…It was found that treatment with 2-DG inhibited the growth of a variety of tumor types in rodents (2,6,17,40,65,66), which led to early trials of 2-DG administration as a single agent in human cancer patients (39). However, the clinical trials were unsuccessful and generated adverse side effects associated with the high drug concentrations required to mimic the antitumor activity observed in the animal studies (1,4,31,32,68). Although the Warburg hypothesis has been elegantly confirmed by positron emission tomography (PET) (34,72), the ineffectiveness of 2-DG monotherapy in killing the tumor is more likely due to glycolysis not being essential for cell survival.…”
Section: The Warburg Effect and 2-dgmentioning
confidence: 99%
“…It was found that treatment with 2-DG inhibited the growth of a variety of tumor types in rodents (2,6,17,40,65,66), which led to early trials of 2-DG administration as a single agent in human cancer patients (39). However, the clinical trials were unsuccessful and generated adverse side effects associated with the high drug concentrations required to mimic the antitumor activity observed in the animal studies (1,4,31,32,68). Although the Warburg hypothesis has been elegantly confirmed by positron emission tomography (PET) (34,72), the ineffectiveness of 2-DG monotherapy in killing the tumor is more likely due to glycolysis not being essential for cell survival.…”
Section: The Warburg Effect and 2-dgmentioning
confidence: 99%
“…The administration of aadrenoceptor blockers counteracted the serum T4 reduction found in SCGx rats during the Wallerian degeneration phase (61). Similarly, during the increased autonomic nerve activity obtained by injecting 2-deoxyglucose into mice, the adrenoceptor blocker phentolamine prevented the inhibition of TSH-induced thyroid hormone release (56). A similar ccadrenergic mediation of NE inhibition of TSH activity on the thyroid was reported in vitro, indicating that the NE exerts a direct modulatory effect on thyroid acini (62).…”
Section: Effect Of Sympathetic Innervationmentioning
confidence: 67%
“…Experiments employing electrical stimulation of SCG in T4-treated mice have indicated a stimulatory activity of noradrenergic nerves in the presence of low or suppressed circulating TSH (54). On the other hand, injection of TSH into mice previously treated with 2-deoxyglucose, a drug that increases peripheral sympathetic activity, failed to augment T4 release (56). Likewise, we reported that in rats having degenerating sympathetic nerve terminals in the SCG field of projection after SCGx, the activity of exogenous TSH to increase T4 release was blunted (12).…”
Section: Effect Of Sympathetic Innervationmentioning
confidence: 99%
“…If the increase in ChAT activity and acetylcholine release found in vitro after T4 exposure of rat SCG are a reflec tion of the in vivo activity of T4 on the sympathetic nervous system, an increase in preganglionic fiber activity will follow the increase of circulating T4 levels. Since it was previously demon strated that the peripheral sympathetic input originating in the cervical sympathetic chain is inhibitory for the hypophysialthyroid axis [7,15], the enhancing effect of T4 on ganglionic neurotransmission may be a part of a negative feedback mecha nism controlling T4 secretion. However, when the pregan glionic supply to any sympathetic ganglia is stimulated, a com plex sequence of postsynaptic potentials is recorded, compris ing in chronological order a fast excitatory postsynaptic potential, a hyperpolarizing slow inhibitory postsynaptic poten tial, and slow and very slow excitatory postsynaptic potentials [32,33[.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that the diurnal rhythmicity in plasma melatonin concentration found in mammals is driven by the sympathetic input derived form SCG [5,6], By employing as a paradigm the changes in hormone secre tion occurring during the wallerian degeneration phase that fol lows superior cervical ganglionectomy, an inhibitory influence of SCG neurons via norepinephrine activity and median emi nence a-adrenoceptors was uncovered for the control of thyroid stimulating hormone (TSH) release [7][8][9], The most feasible lo cation for these ganglionic neurons is the rostral portion of the SCG, projecting to the median eminence through the internal Received: October 16, 1990 Accepted after revision: March 26, 1991 carotid nerve [10,11). Additionally, neurons derived from the middle an d /o r inferior cervical ganglia send their projections through the SCG and the external carotid nerve to reach the thyroid gland [12,13] where they inhibit TSH-driven thyroid hormone release [7,14,15]. The objective of the present study was to search for the existence of effects of thyroxine (T4) and 3,3',5-triiodothyronine (T3) on acetylcholine synthesis and re lease in rat SCG in vitro as a way to evaluate a possible feedback loop linking sympathetic activity with the hypothalamohypophysial-thyroid axis.…”
mentioning
confidence: 99%